(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Recently, usage of medicinal plant extracts and herbs as an alternative natural control agent for commercially existing chemical synthesized drugs in cure of oral infectious diseases like periodontal disease and dental caries has been popularized immensely. The present study was aimed to assess the efficacy of antibacterial potency of Punica granatum peel extracts on five common but major oral pathogenic bacteria such as Streptococcus mutans, Streptococcus sanguinis, Streptococcus salivarius, Streptococcus sobrinus and Streptococcus mitis on carcinogenesis. The anti-microbial activity was investigated using Disc infusion technique by assessing Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The extracts were prepared using water, ethanol and chloroform in different concentration by serial dilution (dilution by one-half) using sterile distilled water solvent. The crude extracts were evaluated on Brain Heart Infusion agar along with Ampicillin as positive control and water as negative control. Results obtained showed that the crude ethanolic, aqueous, chloroform extracts of Punica granatum L. demonstrated broad spectrum of inhibition by showing antibacterial effect against Oral streptococci bacteria. The extracts were found less effective on S. salivarius and more effective on S. sanguis, where ethanol extract showed highest effectiveness even in comparison with Ampicillin. The results exhibited in present research study leads to the scientific evidence for the primeval usage of this plant as a medicinal ethno-nutraceutical and considered to be potent and effectual alternative compared to synthetic medicines.